2014
DOI: 10.1021/jp5018168
|View full text |Cite
|
Sign up to set email alerts
|

Size, Shape, Stability, and Color of Plasmonic Silver Nanoparticles

Abstract: The remarkable relationship between the size, shape, and optical properties of silver nanoparticles is proving to be very useful in a range of high performance applications. Considerable effort and investment are focused on delivering silver nanoparticles with precise morphologies. However, the reliability of these particles is contingent upon the morphological stability, particularly against variations in the thermodynamic environment, such as changes in temperature. Using a combination of computational and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
119
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(130 citation statements)
references
References 104 publications
9
119
0
2
Order By: Relevance
“…Silver and copper are more recent scientific studies, as copper is difficult to make due to its rapid oxidation. A nano-phase diagram of structure versus temperature has been developed for gold and silver from experiments and density functional theory (DFT) [11,12]. A phase diagram for copper has been produced as an alloy with gold for nanoclusters [13].…”
Section: Introductionmentioning
confidence: 99%
“…Silver and copper are more recent scientific studies, as copper is difficult to make due to its rapid oxidation. A nano-phase diagram of structure versus temperature has been developed for gold and silver from experiments and density functional theory (DFT) [11,12]. A phase diagram for copper has been produced as an alloy with gold for nanoclusters [13].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 However, preparation routes unavoidably conduct to NPs showing a shape distribution which induces drastic changes in the optical properties of NP assembly. [19][20][21][22] Indeed, by combining Gibbs free energy calculation to discrete dipole approximation, Noguez et al [23][24][25] have shown that the morphology and so the optical properties of NPs depend on the temperature used to synthesize them. In addition, as reported by Sayah et al, 19 silver prolates grown in a mesoporous silica matrix exhibit a large length distribution which induces an inhomogeneous broadening of the L-SPR bands.…”
Section: Introductionmentioning
confidence: 99%
“…Figure (b) and (c) show UV‐vis absorbance spectra of Ag + ‐PAA thin films after exposure to e‐beam generated plasmas at corresponding ranges of pressures and times. Ag nanoparticles are known to exhibit a characteristic absorbance peak in the range of 350–420 nm . The spectra confirm the presence of the localized surface plasmon resonance (LSPR) band associated with Ag nanoparticles.…”
Section: Resultsmentioning
confidence: 70%